Identification of Technological Pedagogical Content Knowledge of Pre-Service Teacher in English Language Learning - Wahab, Aulia Dwi Amalina; Nurhasanah; Abdul Kadir Jaelani; Baiq Nada Buahana (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to identify the competencies of prospective early childhood teachers in integrating Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), and Technological Pedagogical Content Knowledge (TPACK). This study uses a descriptive method and data is collected through a structured questionnaire. The sample consisted of 20 students from the Early Childhood Teacher Education Study Program, class of 2021. The results of the study show that high performance in TPACK with the "Very Good" category connects strong mastery of Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK) which means that the student is not only proficient in using technology but also in teaching and understanding content very effectively. The "Good" category often shows increased pedagogical and content knowledge and the ability to apply technology better. Meanwhile, students with "Average" performance generally have a basic understanding of all components but still have difficulty integrating them effectively. The “Medium” category appears in the components of Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), and Pedagogical Content Knowledge (PCK). In this case, additional support is needed to improve the skills of prospective teacher students in combining technology, pedagogy, and content.